2020
DOI: 10.1371/journal.pone.0230972
|View full text |Cite
|
Sign up to set email alerts
|

Shaped stone balls were used for bone marrow extraction at Lower Paleolithic Qesem Cave, Israel

Abstract: The presence of shaped stone balls at early Paleolithic sites has attracted scholarly attention since the pioneering work of the Leakeys in Olduvai, Tanzania. Despite the persistent presence of these items in the archaeological record over a period of two million years, their function is still debated. We present new results from Middle Pleistocene Qesem Cave on the use of these implements as percussion tools. Use-wear and abundant bone and fat residues found on ten shaped stone balls indicate crushing of fres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 62 publications
0
34
0
Order By: Relevance
“…Percussion damage and residue patterns demonstrate a direct and clear correspondence of most of the chopping tools with this type of activity. Although pounding activities on bone might also be performed using other types of tools, Layer C3 lacks other core-tool forms such as polyhedrons or spheroids useful for this type of activity [ 81 ], notwithstanding the fact that simple unmodified cobbles or hammerstones could have also been used as complementary items for this kind of task, as shown in our experimental trials (S10 Fig in S1 File ). Chopping tools might have served as one component of a tool-kit oriented towards the extraction of bone marrow, used primarily as sharp-edged chopping tools aimed at fracturing the bone in order to facilitate and guide subsequent blows, conducted by a more massive percussor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Percussion damage and residue patterns demonstrate a direct and clear correspondence of most of the chopping tools with this type of activity. Although pounding activities on bone might also be performed using other types of tools, Layer C3 lacks other core-tool forms such as polyhedrons or spheroids useful for this type of activity [ 81 ], notwithstanding the fact that simple unmodified cobbles or hammerstones could have also been used as complementary items for this kind of task, as shown in our experimental trials (S10 Fig in S1 File ). Chopping tools might have served as one component of a tool-kit oriented towards the extraction of bone marrow, used primarily as sharp-edged chopping tools aimed at fracturing the bone in order to facilitate and guide subsequent blows, conducted by a more massive percussor.…”
Section: Discussionmentioning
confidence: 99%
“…In that case, tools such as shaped stone balls (polyhedrons/spheroids, usually much heavier than the chopping tools, often made of limestone and bearing massive ridges), which make contact with a large area of the bone, allow the force to spread over a large extent of the surface. This makes it possible to split large bones and extract the bone marrow in perfect condition [ 81 ].…”
Section: Methodsmentioning
confidence: 99%
“…It is important to note that full and partial chaînes opératoires of different types of items and tools, made of fresh unpatinated flint, are present at all contexts of the cave, while recycled patinated items amount to c. 12 per cent of all assemblages, indicating a recurrent phenomenon practised in addition to the constant supply of fresh nodules and blanks produced elsewhere than the cave (Barkai et al 2018; Efrati et al 2019). Moreover, it was recently demonstrated that bifaces and shaped stone balls were also collected from older Acheulean sites in the vicinity of the cave for both practical and perceptual reasons (Agam et al 2019; Assaf et al 2020), suggested to be viewed as acts of appreciation towards the functional benefits of these items as well as their ancestral essence.…”
Section: Post-patinated Flaked Items (‘Double Patina’)mentioning
confidence: 99%
“…This Amudian archaeological context is positioned directly below the SW Yabrudian and is extended through squares A-F/15-17; however, faunal analysis included only the squares rich in Spheroids, and only this part of the context is included in this analysis. A concentration of shaped stone balls was recovered from this context (Barkai and Gopher, 2016), and a techno-functional analysis indicated that the stone balls were used in marrow extraction (Assaf et al, 2020).…”
Section: Qesem Cavementioning
confidence: 99%